(untitled) (Eurasian Journal of Ecology, 2018)
The article presents the study results of the antibiotic activity of extracts, culture liquids obtained from 20 different strains of actinomycetes of the genus Streptomyces isolated from different types of soils in the Almaty and Kostanai regions of Kazakhstan, against the causative agent of the Erwinia amylovora fire blight. It was found that the extracts of strains studied inhibited the growth of Erwinia amylovora to a greater or lesser extent. While the extracts of strains No. 7, 9 and 28 isolated from the sandy soil of Ili district of Almaty region possessing the greatest antibiotic activity. The growth inhibition zones of Erwinia amylovora as a result of their effect were 18.3 mm, 21.3 mm and 14.3 mm, respectively. In the variant with the reference product of the Russian production «Fitolavin», recommended for use against fire blight of fruit crops and taken for comparison, the average size of the growth inhibition zone of the causative agent of fire blight was 13.5±0.29 mm, which is 1.57 times less, than in the case of using the extract of strain No. 9. These strains can later be used for the development of products intended for biocontrol over the spread of fire blight of fruit crops in Kazakhstan. Key words: fruit crops, fire blight, actinomycetes, Streptomyces, extract, antibiotic activity, growth inhibition.